2019
DOI: 10.1128/iai.00113-18
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Impairs IgG1-Mediated Phagocytosis and Killing of Cryptococcus neoformans by J774.16 Macrophage- and NR-9640 Microglia-Like Cells

Abstract: The prevalence of methamphetamine (METH) use is estimated at ∼35 million people worldwide, with over 10 million users in the United States. Chronic METH abuse and dependence predispose the users to participate in risky behaviors that may result in the acquisition of HIV and AIDS-related infections.Cryptococcus neoformansis an encapsulated fungus that causes cryptococcosis, an opportunistic infection that has recently been associated with drug users. METH enhancesC. neoformanspulmonary infection, facilitating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…It is possible that the maintenance of B cells in the lungs and spleen is related to the accumulation of METH in these tissues and the sensitivity of other cells to the drug. METH induces apoptosis in macrophages ( Aslanyan et al, 2019 ) and T cells ( Potula et al, 2010 ). However, B cell viability in vitro is only affected by a significantly high METH concentration (100 μM) or four times the concentration (25 μM) used in our studies ( House et al, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that the maintenance of B cells in the lungs and spleen is related to the accumulation of METH in these tissues and the sensitivity of other cells to the drug. METH induces apoptosis in macrophages ( Aslanyan et al, 2019 ) and T cells ( Potula et al, 2010 ). However, B cell viability in vitro is only affected by a significantly high METH concentration (100 μM) or four times the concentration (25 μM) used in our studies ( House et al, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…METH has important implications on Ab production ( Wey et al, 2008 ; Martinez et al, 2009 ), phagocytic responses ( Mihu et al, 2015 ), and the fate of pathogens ( Aslanyan et al, 2019 ) during infection. In addition, Ab isotype might be critical in stimulating the phagocytic cell migration and antimicrobial effector functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binge doses of 260 to 1,000 mg produce 17 to 80 μM blood METH levels and levels in the micromolar range of hundreds in organs ( 64 ). Thus, we selected 2.5 to 10 mg of METH/kg of body weight/day to perform our in vivo experiments ( 24 ) and 25 μM METH to perform our in vitro experiments ( 65 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, there is some evidence that illicit drug use alone or in conjunction with HIV, may also contribute to the development of cryptococcosis. Related to immunoglobulin defects, the use of methamphetamine (METH) has been shown to impair IgG-mediated phagocytosis and killing of cryptococcal cells in murine models while also facilitating intracellular replication [ 187 , 188 ]. In addition, murine models have also shown that METH enhances PC infection and dissemination to the CNS through alteration of cryptococcal virulence factors (e.g., capsule composition and capsule shedding) and by reducing the integrity of the host blood brain barrier [ 189 , 190 ].…”
Section: Associations Between Human Attributes and Cryptococcosismentioning
confidence: 99%